Profitability Analysis of Major Crops Cultivated in Assam: Evidence from the analysis of primary data Submitted By - Mr. Hitesh Barman, Dr. Archana Sharma (International Journal of Modern Agriculture, 2021)
The study analysed the profitability of various crops cultivated by the farmers and the factors influencing of farm profitability. Multi-stage sampling was used and 60 farmers were sampled randomly to collect information relevant for the study. The study also used CACP Cost concept to calculate cost of cultivation and used multiple regression analysis to find out factor influencing farm profitability. Study indicated large variation of cost of cultivation among the category of farmers; it was mainly due to difference in use of fertilizer, seeds, rental value of land, use of human labour, interest on fixed capital etc. it also revealed that farmers got reasonable profit and were economically viable and sustainable by cultivating Spice, Brinjal, Tomato, Potato etc. as compared to other crops. The results of the multiple linear regression analysis revealed that Education of farmers, Farming experience, Agricultural training, Extension Services, Farm mechanization, Awareness about MSP, had a direct relationship with profitability age, Land size, Distance from home to Market place had negative influence on farm profitability. The study recommended for encouraging farmers to use more area on vegetables or horticultural crops rather than paddy and oilseeds, for better profit and sustainability of farming.